2008
DOI: 10.1371/journal.pgen.1000314
|View full text |Cite
|
Sign up to set email alerts
|

Physcomitrella patens DCL3 Is Required for 22–24 nt siRNA Accumulation, Suppression of Retrotransposon-Derived Transcripts, and Normal Development

Abstract: Endogenous 24 nt short interfering RNAs (siRNAs), derived mostly from intergenic and repetitive genomic regions, constitute a major class of endogenous small RNAs in flowering plants. Accumulation of Arabidopsis thaliana 24 nt siRNAs requires the Dicer family member DCL3, and clear homologs of DCL3 exist in both flowering and non-flowering plants. However, the absence of a conspicuous 24 nt peak in the total RNA populations of several non-flowering plants has raised the question of whether this class of siRNAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
97
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 70 publications
(102 citation statements)
references
References 53 publications
5
97
0
Order By: Relevance
“…However, homologs of key genes known to be responsible for hcsiRNA biogenesis and function in angiosperms clearly exist in diverse plant lineages (Zong et al, 2009;Banks et al, 2011;Huang et al, 2015;Wang and Ma, 2015;You et al, 2017). Reverse genetic analyses of these homologs, coupled with sRNA-seq analyses of the mutants, has shown that hc-siRNAs exist in the moss P. patens (Cho et al, 2008;Coruh et al, 2015), which implies that the pathway was most likely present in the last common ancestor of all land plants. Whether hc-siRNAs have been specifically lost in the conifers and/or ferns remains an open question, but the presence of high levels of 24 nt RNAs in specific tissues of the conifers Norway spruce (Picea abies) (Nystedt et al, 2013) and Japanese larch (Larix leptolepis) (Zhang et al, 2013) suggests that this may not be the case.…”
Section: Conservation Evolution and Annotations Of Endogenouse Sirnasmentioning
confidence: 99%
“…However, homologs of key genes known to be responsible for hcsiRNA biogenesis and function in angiosperms clearly exist in diverse plant lineages (Zong et al, 2009;Banks et al, 2011;Huang et al, 2015;Wang and Ma, 2015;You et al, 2017). Reverse genetic analyses of these homologs, coupled with sRNA-seq analyses of the mutants, has shown that hc-siRNAs exist in the moss P. patens (Cho et al, 2008;Coruh et al, 2015), which implies that the pathway was most likely present in the last common ancestor of all land plants. Whether hc-siRNAs have been specifically lost in the conifers and/or ferns remains an open question, but the presence of high levels of 24 nt RNAs in specific tissues of the conifers Norway spruce (Picea abies) (Nystedt et al, 2013) and Japanese larch (Larix leptolepis) (Zhang et al, 2013) suggests that this may not be the case.…”
Section: Conservation Evolution and Annotations Of Endogenouse Sirnasmentioning
confidence: 99%
“…Small RNAs homologous to Helitron sequences have been described from maize (67), A. thaliana (134), Phytophthora species, (187,188) and Physcosmitrella patens (189). Generally it is surmised that one kind of small RNA (small interfering (siRNA)) regulate TE expression.…”
Section: Host Gene Regulation As a Consequence Of Gene Capturementioning
confidence: 99%
“…wild-type 10-d-old protonemata (NCBI GEO GSM313212) (Cho et al 2008). This had the effect of removing from consideration MIRNAs which were not highly expressed in the tissue from which the degradome sample was taken.…”
Section: Remnants Of Mirna Hairpin Processing In Degradome Datamentioning
confidence: 99%
“…Wild-type 10-d-old Physcomitrella patens (Gransden) protonemata were cultured, harvested, and total RNA extracted as previously described (Cho et al 2008). Approximately 200 ng of polyA-enriched RNA were directly ligated to a chimeric DNA/ RNA adapter containing a 39 EcoP15I site using T4 RNA Ligase 1 (New England Biolabs).…”
Section: Degradome Library Constructionmentioning
confidence: 99%